Contradiction and time in recentivism - Bańka, Józef (Folia Philosophica, 2011)
The paper draws upon so-called disscusive logic which does not refute the principle of contradiction directly, but accepts contradicting statements of different parties of the discourse or of the same subject but in different time. On the ground of recentivism every statement contrary to the system is sifted through the axiology of the system in a recentiori mode. That is, it is rejected by the system just as it falls into contradiction in the moment of being expressed (sermo). In short: the moment of expression eliminates contradiction in the content, for according to recentivist epistemology the description of an event is not true or false in general, but in the present time only and it changes its truthfulness with the time.